Critical Examination of Müller Glia-Derived in vivo Neurogenesis in the Mouse Retina - Xie, Ye; Chen, Bo (Frontiers in Cell and Developmental Biology, 2022)
Significant progress has been made in recent years to unlock the regenerative capabilities of MG (Muller glia) in the mouse retina. In this minireview, we plan to discuss current research progress on Muller glia-derived neurogenesis in the mouse retina, focusing on stringent experimental methods, especially the fate mapping techniques, that can be used to evaluate and validate whether de novo regeneration of retinal neurons indeed takes place from Muller glia. These evaluation criteria will be used to evaluate research reports on MG-derived regeneration of photoreceptors, retinal inter-neurons, and retinal ganglion cells.